Penerapan Pertanggungjawaban Pidana Korporasi Dalam Tindak Pidana Penggelapan Dana Pihak Ketiga Di Perbankan - Yevendri Yevendri (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
In an effort to collect funds, banks must recognize the sources of funds that exist in various levels of society in different forms. One of them is third party funds. These funds must be managed well, because they are temporary and must be returned, meaning that the bank as the holder of third party funds must be responsible for the safety of these third party funds. However, incident after incident has befallen the existence of these third party funds, one of which is the occurrence of a criminal act of embezzlement of third party funds committed by the defendant with the initials HAW, an employee of the BRI Watampone Branch, who was examined and tried by the Watampone District Court in Watampone, in Decision Number 387 / Pid.B / 2012 / PN.Wtp. which stated that the defendant with the initials HAW was guilty of committing the crime of